Cost-effectiveness of options for reducing health risks in areas where food crops are irrigated with treated or untreated wastewater - Drechsel, Pay; Seidu, R. (Informa UK Limited, 2011)
In this article the authors draw from a comparative assessment of different interventions, examining their costs, risk-reduction potential and cost-effectiveness. They consider a case study in Ghana, using an approach that integrates quantitative microbial risk assessment (QMRA), disability-adjusted life years (DALYs) and cost-effectiveness analysis. Most practices appear highly cost-effective, although only a few are likely to avert more than 80% of the DALY burden. As compliance will always be a challenge, the results support the need for a multi-barrier risk-management approach that, where possible, combines treatment and non-treatment interventions.